ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE RGEC DAN PENGARUHNYA TERHADAP PERTUMBUHAN LABA (STUDI KASUS : PADA PT BANK DKI) - Amperaningrum, Izzati; Wiratno, Adi (Soedirman Accounting, Auditing and Public Sector Journal, 2024)
The purpose of this study is to analyze the effect of NPL (Non Performing Loan), GCG (Good Corporate Governance), ROA (Return On Assets), and CAR (Capital Adequacy Ratio) on Profit Growth at PT Bank DKI. The analysis method in this study uses quantitative secondary data. The sampling method uses a purposive sampling technique where it can be Bank DKI who is the sample in this study. The selected samples were then analyzed using normality test, multicollinearity test, heteroskedasticity test, autocorrelation test, multiple linear regression test, coefficient of determination test, F test, and t test with tools help process the SPSS data. The results showed that the ROA (Return On Assets) variable partially affected Profit Growth. Meanwhile, NPL (Non Performing Loan), GCG (Good Corporate Governance), and CAR (Capital Adequacy Ratio) partially have no effect on Profit Growth. Simultaneously, NPL (Non Performing Loan), GCG (Good Corporate Governance), ROA (Return On Assets), and CAR (Capital Adequacy Ratio) affect Profit Growth. The ability of independent variables to explain the variation of dependent variables is 66% while the remaining 34% is the contribution of other variables that are not included in this study.